2014
DOI: 10.1002/jwmg.655
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal field use by fall migrating American woodcock in the Delta of Arkansas

Abstract: The American woodcock (Scolopax minor) population has declined since the late 1960s across its range and is now considered a species of special concern. Research on woodcock habitat use during migration and migratory routes through the Central Flyway has been limited. We assessed woodcock phenology, estimated density, and nocturnal habitat use in fields on public lands in the lower Mississippi Alluvial Valley portion of Arkansas during November and December of 2010 and 2011. We used all‐terrain vehicles to sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Although mow treatments did not provide foliar volume above 0.5 m, woody debris both standing and on the ground and dead clump grasses likely provided adequate vertical cover while also allowing feeding. Studies in Virginia (Krementz et al 1995), North Carolina (Stribling and Doerr 1985, Blackman et al 2013, and Arkansas (Krementz et al 2014) have reported woodcock use of agricultural fields with ridge/furrow topography and residual vegetation that likely provides a better vertical cover component than did our disk treatment.…”
Section: Discussionmentioning
confidence: 57%
“…Although mow treatments did not provide foliar volume above 0.5 m, woody debris both standing and on the ground and dead clump grasses likely provided adequate vertical cover while also allowing feeding. Studies in Virginia (Krementz et al 1995), North Carolina (Stribling and Doerr 1985, Blackman et al 2013, and Arkansas (Krementz et al 2014) have reported woodcock use of agricultural fields with ridge/furrow topography and residual vegetation that likely provides a better vertical cover component than did our disk treatment.…”
Section: Discussionmentioning
confidence: 57%
“…Proximity to fields and clearings may also play a large role in the selection of diurnal habitat. While it is well established that woodcock often utilize agricultural fields at night (Blackman et al 2011, Krementz et al 2014, woodcock may use a wide variety of other fields and clearings which may be more difficult to quantify on the landscape (Berdeen andKrementz 1998, Masse et al 2013). Given these challenges, in situations in which vegetation metrics at paired samples are taken for comparison to habitat for individual woodcocks, we recommend that a minimum buffered radius of 43 m from the flush location, or an unsampled area covering approximately 0.58 ha (equivalent to our largest diurnal MCP) centered on the flush location, would ensure minimal overlap between areas likely used and random locations.…”
mentioning
confidence: 99%